HUMANIZATION: THE POSITIVE CHANGE THAT NURSES CAN BRING TO THE PATIENT’S LIFE - Garbo Pinto, Elda; Aguiar Sanches, Cinthia; Aparecida Braga de Oliveira, Elcie; Gomes da Silva, Paula; Cristina dos Santos Darruiz, Katia; de Oliveira Florentino, Anelvira; da Costa, Natanael; Lopes, Chilerne; Rosana Trevisani Corrêa, Cláudia; Marques da Rocha Hoelz, Cássia (Health and Society, 2024)
Introduction: Humanization in nursing care has gained prominence as an essential strategy to improve the quality of healthcare services. The practice of humanization considers not only the technical aspects of care but also the emotional, social, and spiritual elements of the patient, promoting a more comprehensive and personcentered approach. Objectives: To analyze the contributions of humanization in emergency, urgent care, and intensive care services, highlighting its positive impacts on patients’ lives and nursing practice. Methodology: This is a type of bibliographic study, with a descriptive methodological approach, with searches in health databases. The sample consisted of eight articles selected and reviewed between August and October 2024.Results: The analysis of the research indicates that humanization, when systematically applied, produces significant outcomes, such as strengthening the bond between nurses and patients, improving the quality of care, and enhancing user satisfaction. However, challenges were also identified, including a lack of resources and training, which hinder the full implementation of this approach. Humanization involves not only adhering to policy guidelines but also adopting compassionate practices, effective communication, and holistic care, factors that make the hospital environment more welcoming and efficient. Final Considerations: Despite the obstacles encountered, humanization has the potential to transform the patient experience and improve the quality of work for nursing professionals. Continuous efforts are essential to strengthen this approach in various healthcare contexts.